DNA triple-helix formation at target sites containing duplex mismatches. - Rusling, D; Brown, T; Fox, K (2006)
We have studied the formation of DNA triple helices at target sites that contain mismatches in the duplex target. Fluorescence melting studies were used to examine a series of parallel triple helices that contain all 64 N.XZ triplet combinations at the centre (where N, X and Z are each of the four natural DNA bases in turn). Similar experiments were also performed with N=bis-amino-U (BAU) (for stable recognition of AT base pairs) and N=S (for recognition of TA inversions). We find that the introduction of a duplex mismatch destabilises the C+.GZ, T.AZ and G.TZ triplets. A similar effect is seen with BAU.AZ triplets. In contrast, other base combinations, based on non-standard triplets such as C.AZ, T.TZ, G.CZ and A.CZ are stabilised by the presence of a duplex mismatch. In each case S binds to sites containing duplex mismatches better than the corresponding Watson-Crick base pairs.